Diastereoselective Addition of PhSCF2SiMe3to Chiral N- tert-Butanesulfinyl Ketimines Derived from Isatins: Synthesis of Enantioenriched gem-Difluoromethylenated Spiro-pyrrolidinyl and Spiro-piperidinyl Oxindoles - Keereewan S. (2023)
A convenient and efficient synthetic strategy to prepare enantioenriched gem-difluoromethylenated spiro-pyrrolidinyl and spiro-piperidinyl oxindoles is described. Fluoride-mediated diastereoselective nucleophilic addition of PhSCF2SiMe3to chiral N-tert-butanesulfinyl ketimines derived from isatins was a key step and provided diastereomeric adducts, which were readily separable. Removal of the chiral sulfinyl group followed by structural manipulation afforded chiral gem-difluoromethylenated spiro-pyrrolidinyl and spiro-piperidinyl oxindoles.